Characterization of miRNA profiling in konjac-derived exosome-like nanoparticles and elucidation of their multifaceted roles in human health - Shen, Chuan; Li, Xia; Qin, Jianfeng; Duan, Longfei (Frontiers in Plant Science, 2024)
Plant-derived exosome-like nanoparticles (ELNs) have demonstrated cross-kingdom capabilities in regulating intercellular communication, facilitating drug delivery, and providing therapeutic interventions in humans. However, the functional attributes of konjac-derived ELNs (K-ELNs) remain largely unexplored. This study investigates the isolation, characterization, and functional analysis of K-ELNs, along with the profiling and differential expression analysis of associated miRNAs in both K-ELNs and Konjac tissues. K-ELNs were successfully isolated and characterized from two konjac species using ultracentrifugation, followed by Transmission Electron Microscopy (TEM) and Nanoparticle Tracking Analysis (NTA). Small RNA sequencing identified a total of 3,259 miRNAs across all samples. Differential expression analysis revealed significant differences in miRNA profiles between K-ELNs and tissue samples. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analysis of target genes provided insights into their roles in modulating pathways associated with diseases such as cancer and neurodegenerative disorders. Additionally, six miRNAs were selected for validation of sequencing results via RT-qPCR.The 5'RLM-RACE method was employed to validate the cleavage sites between differentially expressed miRNAs (DEMs) and their predicted target genes, further substantiating the regulatory roles of miRNAs in konjac. The findings of this study enhance our understanding of the molecular mechanisms underlying the biological functions and applications of K-ELNs, laying the groundwork for future research into their potential therapeutic roles in human health.